Co-movements in stock market returns, Ireland and London 1869–1929. (11th September 2017) - Stuart, Rebecca
Abstract : This article studies the relationship between the Irish and London stock markets over the period 1869 to 1929, using monthly data on capital gains. A bivariate GARCH model shows that there were significant volatility spillovers from the London to the Irish market, but not vice versa. This suggests that shocks originating in London were transmitted to Ireland, but that the reverse did not occur. Furthermore, the time-varying correlation indicates that the co-movement between London and Ireland declined during the Irish independence struggle and the establishment of the Irish Free State. The correlation appears to stabilise in the late 1920s.